A Project feasibility study on a Drive-In Movie Theater - Cruz, Christian Joseph R. (College of Engineering, 1995)
In order to meet the requirements of course (I.E. 153: Project Feasibility Study), two undergraduate Industrial Engineering students have undergone an extensive feasibility study on a drive-in theater. Initially, the proponents of the study have proposed five venture ideas for the course and after conducting a selection process have found the drive-in theater as a more favorable project for a feasibility analysis. After the product or service venture was selected, a market study was conducted in the course of about one month. Surveys and data collection from applicable institutions were conducted to determine the marketability of the project. After careful analysis, the market for the venture has been determined and analyzed to exist in the setting chosen by the study group (Metro Manila). When the market for a drive-in facility has been analyzed as feasible, a technical analysis was immediately done to determine whether the local setting has the means and capability of providing the needed technology and equipment for the implementation of the facility. A thorough investigation was done regarding existing institutions related to the project. The study group was able to come up with adequate information to conclude that although most of the equipment and technology needed for the drive-in theater are not locally available, these can be readily imported and installed by existing and highly recommended distributors of theater equipment in Metro Manila. With this information and other technical requirements analyzed by the group in the course of one month, it was concluded that the venture is technically feasible. The financial and socio-economic feasibility analysis was the next step conducted for the last month of the course. By laying down the major assumptions and then simulating the implementation and running of the drive-in theater, the profitability of the venture was analyzed and evaluated as very favorable. The expectation of the study group regarding the returns on investments that the project will generate was exceeded. Furthermore, the socio-economic contribution of the project was analyzed to be favorable not only to the target users of the facility but also and more importantly to the government and society in general. The final conclusion for the project is that the drive-in theater is a feasible project that would generate a very profitable income for future investors.